(3JGQjN Gdedc GdCTQa bGjJHGjs
(3ChdgG (B:s
(3hHYO , adeG cGf GdYOd ef egeGJ GdOjf CMHHJ Cf UOQJ gPG GdcJGH HEjQGO TF eeG jHYK Ydjg s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B30 ; (3HQhcdeGf edMb (B- - (3U (B26 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B88 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs